77 Best Practices in Negotiation - Goodman, Gary (Ascent Audio, 2019)
Dr. Gary S. Goodman is the bestselling author of twelve books and thousands of articles. He is also creator of the applauded training program, "Best Practices In Negotiation," offered at U.C. Berkeley and UCLA Extension, as well as at organizations worldwide. As an attorney, Fortune 1000 management consultant, and celebrated speaker and lecturer, Dr. Goodman has personally negotiated more than a thousand contracts, for his companies and for his clients. Drawing from the best published sources and his own ample experience, Dr. Goodman shares tips and techniques for negotiating everyday transactions as well as mega-deals. He explains the six-step Anatomy of a Negotiation Transaction, which guides you from the inception to the execution of agreement, while enabling you to avoid common pitfalls and dirty tricks. If you want better bargains on cars and housing, you need look no farther. Having sold cars and real estate, the author gives you unique and counter-intuitive advice, plus he divulges those situations in which he has failed to negotiate up to his own professional standards.